The Role of Maternal Literacy in Child Health Outcomes in Developing Countries: A Systematic Review - Shiva Aflahiyah (Universitas Satya Terra Bhinneka, 2026)
Introduction/Main Objectives: Child health remains a major public health priority in developing countries. Maternal literacy has been recognized as a modifiable determinant influencing child health through caregiving practices and health-related decision-making. Background Problems: Although several studies have examined maternal literacy and child health outcomes, the evidence has not been systematically synthesized across different research settings or geographical contexts. Novelty: This review provides a comprehensive synthesis of the association between maternal literacy and child health outcomes in developing country contexts. Research Methods: A systematic review was conducted following PRISMA guidelines using cross-sectional studies published between 2015 and 2026. Articles were retrieved from PubMed, ScienceDirect, Springer, and Garuda databases, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Finding/Results: Ten studies met the inclusion criteria. Higher maternal literacy—including health, nutrition, food, electronic, and oral health literacy—was consistently associated with improved child health outcomes. Significant associations were observed with complete child immunization (p = 0.042; aOR = 0.21; 95% CI: 0.17–0.73), improved child nutritional status (p < 0.05), reduced odds of childhood overweight and obesity (aOR = 0.29; 95% CI: 0.17–0.51; p < 0.001), optimal early childhood development (aOR = 2.16; 95% CI: 1.29–3.61), and lower dental caries prevalence (p < 0.05). Conclusion: Maternal literacy plays a critical role in shaping child health and development, highlighting its importance as a target for child health interventions in developing countries. Keywords: Maternal literacy; Child health; Health literacy; Developing countries; Systematic Review.